Antenatal depression programs cortisol stress reactivity in offspring through increased maternal inflammation and cortisol in pregnancy: The Psychiatry Research and Motherhood – Depression (PRAM-D) Study. (December 2018) - Osborne, S.; Biaggi, A.; Chua, T.E.; Du Preez, A.; Hazelgrove, K.; Nikkheslat, N.; Previti, G.; Zunszain, P.A.; Conroy, S.; Pariante, C.M.
Highlights: Women with antenatal depression have higher stress-related biomarkers than controls. Women with antenatal depression have shorter length of gestation than controls. Neonates exposed to antenatal depression have suboptimal neurobehavioural function. 1-year-olds exposed to antenatal depression have increased cortisol stress-response. Maternal antenatal, and infant stress-related biomarkers are associated. Abstract: Introduction: Antenatal depression is associated with a broad range of suboptimal outcomes in offspring, although the underlying mechanisms are not yet understood. Animal studies propose inflammation and glucocorticoids as mediators of the developmental programming effect of prenatal stress on offspring stress responses, but studies in humans are not yet at this stage. Indeed, to date no single study has examined the effects of a rigorously defined, clinically significant Major Depressive Disorder (MDD) in pregnancy on maternal antenatal inflammatory biomarkers and hypothalamic-pituitary (HPA) axis, as well as on offspring HPA axis, behavior and developmental outcomes in the first postnatal year. Methods: A prospective longitudinal design was used in 106 women (49 cases vs. 57 healthy controls) to study the effect of MDD in pregnancy and associated antenatal biology (inflammatory and cortisol biomarkers), on offspring stress response (cortisol response to immunization, at 8 weeks and 12 months), early neurobehavior (Neonatal Behavioral Assessment Scale, NBAS, at day 6), and cognitive, language and motor development (Bayley Scales of Infant and Toddler Development at 12 months). Results: Compared with healthy controls, women with MDD in pregnancy had raised interleukin (IL) IL-6 (effect size (δ) = 0.53, p = 0.031), IL-10 (δ = 0.53, p = 0.043), tumor necrosis factor alpha (δ = 0.90, p = 0.003) and vascular endothelial growth factor (δ = 0.56, p = 0.008), together with raised diurnal cortisol secretion (δ = 0.89, p = 0.006), raised evening cortisol (δ = 0.64, p = 0.004), and blunted cortisol awakening response (δ = 0.70, p = 0.020), and an 8-day shorter length of gestation (δ = 0.70, p = 0.005). Furthermore, they had neonates with suboptimal neurobehavioral function in four out of five NBAS clusters measured (range of δ = 0.45–1.22 and p = 0.049–<0.001) and increased cortisol response to stress at one year of age (δ = 0.87, p < 0.001). Lastly, maternal inflammatory biomarkers and cortisol levels were correlated with infant stress response, suggesting a mechanistic link. Conclusion: This study confirms and extends the notion that depression in pregnancy is associated with altered offspring behavior and biological stress response, and demonstrates that changes in maternal antenatal stress-related biology are associated with these infant outcomes.